Spin Pumping and Inverse Spin Hall Effect in Iridium Oxide. Issue 9 (29th June 2021) - Sahoo, Biswajit; Roy, Koustuv; Gupta, Pushpendra; Mishra, Abhisek; Satpati, Biswarup; Singh, Braj Bhusan; Bedanta, Subhankar
Abstract: Large spin‐to‐charge conversion (spin Hall angle) and spin Hall conductivity are prerequisites for development of next generation power efficient spintronic devices. In this context, heavy metals (e.g., Pt, W, etc.), topological insulators, and antiferromagnets are usually considered because they exhibit high spin–orbit coupling (SOC). In addition to the above materials, 5d transition metal oxide, for example, iridium oxide (IrO2 ) is a potential candidate which exhibits high SOC strength. Here a study of spin pumping and inverse spin Hall effect (ISHE), via ferromagnetic resonance (FMR), in IrO2 /CoFeB system is reported. By investigating the in‐plane angular dependence of the ISHE voltage, the individual contribution of spin pumping and other spin rectification effects in the magnetic layer is identified. The authors' analysis shows significant contribution of spin pumping effect to the ISHE signal. It is shown that polycrystalline IrO2 thin film exhibits high spin Hall conductivity and spin Hall angle which are comparable to the values of Pt. Abstract : Iridium oxide (IrO2 ) has the potential to be used in spintronic devices for efficient charge‐to‐spin conversion due to its high spin–orbit coupling. This work demonstrates spin pumping in IrO2 /CoFeB bilayers via ferromagnetic resonance. Electrical detection of voltage arising from efficient spin‐to‐charge conversion via inverse spin Hall effect is used to quantify the spin Hall angle in this system.